Analisis Beban Kerja Petugas Rekam Medis Dengan Menggunakan Metode Wisn dan Fishbone di Puskesmas Ambulu Tahun 2019 - Raisa Putri Ramadhani; Rinda Nurul Karimah; Nugroho Setyo Wibowo; Andri Permana Wicaksono (Politeknik Negeri Jember, 2020)
The existing problem that related to workload of medical records officer in Primary Health Care of Ambulu there are never done the analysis and evaluation, more over since 2018 medical record unit and registration unit splinted into two unit to be on oneâ€™s own. This research that intend to do the analysis workload of medical record officers therfore be discovered the level of workload of officer with WISN (workload indicator staff need) methode. If ther is already known the workload of medical record officers the next is an analysis of causative factors of workload was carried out withÂ fishbone methode with approach ofÂ 5M (man, money, methode, material, mechine) and then the next with FGD (focus group discusion) to determine the main priority that caused workload so that improvements of workload can be made. The type of this research is a qualitative with collecting data tecnic in the form of observation, interview, documentation, and FGD. The subject of this research are 3 medical record officer, there are 1 medical recorder and 2 medical recorder helper. The based on this research workload analysis the job description is well done because in the job description there is no division of tasks according to posisition so completion of the task have done together. The result of the calculation of workload is knowing the amount of officer needs the results obtined ideal number of officers there are 4,85 there for be rounded to 5 so the conclusion is the workload in the unit medical record is high with rhe total 0,6. The efforts to improve the workload including addition of human resources and the held of training thus increasing the knowledge and skills of officers.